CROSS-CULTURAL IMPLICATIONS OF THE PATTERNS OF GERMAN UTTERANCES IN TOUR GUIDING IN INDONESIA - Mery Dahlia Hutabarat (LITERA, 2016)
The purpose of this study is to describe the patterns of German utterances in tour guiding related to cross-cultural aspects. This was a qualitative descriptive study in whichthe data were collected through interviews and questionnaires. The findings show thatthe cross-cultural implications are manifested by tour guides’ utterances to prepare avisit a tourist attraction. The utterances contain suggestion, information, and prohibitionon doing things inappropriate for Indonesian culture such as how to shake hands anddress properly in a temple. Most utterances use the infinitive construction without asubject. They are communicative and understandable to German tourists. The utterances,however, do not seem to be polite enough based on German grammatical rules. Therefore, the patterns of utterances are designed for prospective German language speaking tour guides to learn.